Premises and Limitations of Free Public Transport Implementation - Grzegorz Dydkowski; Jozef Gnap (Communications - Scientific letters of the University of Zilina, 2019)
For many years issues of the free provision of transport services, including urban public transport, were outside the main trends of transport economics considerations. However, nowadays, the discussion is ongoing related to usefulness and limitations of the free urban public transport implementation. Protection of the city environment, reduction of personal cars traffic, and increased accessibility and mobility in cities are given as premises for such solution introduction. However, assessments of introduced solutions may not necessarily confirm the assumptions made. Financial problems and those in provision of services - characteristic of goods and services provided for free - add to that. The paper has undertaken the issue related to premises and limitations related to introduction of the fare free urban public transport in regard to the pursuit of effectiveness in the public management.